Numerical Solution of Boundary Problem Pertaining to Two-Dimensional Temperature Pattern with Internal Heat Sources - R. I. Esman (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2008)
The paper contains a mathematical model and a numerical solution of non-stationary heat conduction with variable heat sources that are acting during the whole hardening process. In this case movement of the front of phase transformations along board section is taken into account.The developed mathematical model is applied for calculation of temperature patterns and temperature stresses while obtaining gypsum boards of groove and ridge design.